Tingkat Kecemasan Menghadapi Dunia Kerja pada Mahasiswa Akhir Prodi Bimbingan Konseling Pendidikan Islam UIN Sumatera Utara Medan - Anggini, Yulita Cita; Syarqawi, Ahmad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study was to find out and explain the level of anxiety facing the world of work in final students of Islamic Education Counseling Guidance Study Program at UIN Sumatra Utara Medan. The research method used is descriptive quantitative. Final students of the Islamic Education Counseling Guidance Study Program at UIN Sumatra Utara Medan participated as research subjects. The sample is determined by using purposive sampling. The number of samples is 137 people, 21 men and 116 women. Data for this study were collected using a questionnaire that was distributed online through the Google-Form media. The results of the study revealed that the level of anxiety in facing the world of work for final students of Islamic Education Counseling Guidance Study Program at UIN Sumatra Utara Medan was moderate, with 83 students (60.6%) included in this category.